Cyprus : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This Selected Issues paper examines the adequacy of Cyprus' economic competitiveness. The paper looks at the recent behavior of conventional indicators of competitiveness, estimates Cyprus' equilibrium real exchange rate, and provides an econometric analysis of the main determinants of service exports. The overall conclusion is that the country's current level of the real effective exchange rate is in line with savings-investment fundamentals, but that the recent unfavorable trends in public savings and relative unit labor costs should be reversed to avoid problems in the medium term. The paper also analyzes the financial reform in Cyprus.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet